Liberalisme dan Kesadaran Naif; Studi Kritis Pemikiran Pendidikan John Locke Dan John Dewey - Raikhan, Raikhan (Program Studi Pendidikan Agama Islam (PAI) Fakultas Tarbiyah dam Ilmu Keguruan Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2021)
This paper aims to assess the thoughts of two liberal figures related to the strengths and weaknesses of thought in the context of modern education. In this paper , the author tries to explore deeper and more broadly related to Liberal ideology and paradigm through two cross - age figures , namely the modern era and the contemporary era . The method used in this research is library research. Although these two Liberal figures have different views; namely John Locke is referred to as the main character of empiricism in education and John Dewey is referred to as an instrumental figure in education, but in O'neil's book these two figures fall into the category of Liberal figures, both of which complement each other. The final conclusion in this study is the modernization and renewal of learning centered on individual freedom, say student centered education - the problems that occur in society are not diminishing or disappearing, but from day to day they increase and accumulate, the philosophy of constructivism is that each child constructs own knowledge, it turns out that the goal is to humanize humans to fail, to produce people who highlight the competitive side and education capitalism